Music therapy as a bridge from inpatient to community youth mental health contexts. (1st June 2016) - Hense, Cherry
Abstract : Background : There is growing dialogue about the benefits of music therapy for facilitating young people's recovery from mental illness. Studies highlight the need for continuity of services from inpatient care through to community life. However, youth music therapy programs are typically confined to inpatient settings, with limited progression into community contexts. Objective : This presentation will report on the first stage in a postdoctoral research project at The University of Melbourne, in which a systemic model of youth music therapy services is being developed to better facilitate young people's transition from inpatient services into everyday community participation. Methods : A community music therapy program was piloted in partnership with music agencies and youth mental health services. A critical grounded theory method was used to collect and analyze focus group data in ways that facilitated young people's collaborative input into the research findings. Findings and discussion : Findings will be presented as a theoretical model of how music participation can foster bridging into community engagement. Discussion will focus on the role of systemic models of music therapy in bridging the sociocultural and health factors of inpatient to community contexts.